Analisis Akad Murabahah Pada Produk Pembiayaan KPR BSI Griya Simuda - Hidayatullah Silva Roziannur; Syofia Ulfah (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
Islamic teachings prioritize justice and honesty in all aspects of human life, one of which is Islamic banking. The murabahah agreement on the Griya Simuda KPR product is now starting to become well-known among the public, but in the process there are still indications of an increase in installments or prices in the following years. Bank Syariah Indonesia determines selling price and margin policies that are inseparable from interest rates and competitor levels. This research aims to determine the mechanism of the murabahah contract for the Griya Simuda KPR product and how the contract is implemented, whether it is in accordance with sharia and applicable regulations. The method used in this research is a qualitative approach with library research and data sources obtained from primary data (secondary data). The data collection techniques in this research are documentation and interviews with data analysis, namely content analysis with the presentation of data. Based on the study carried out, it can be concluded that the first analysis of the murabahah contract on the Griya Simuda KPR product is categorized as a bilwakalah murabahah contract which is in accordance with sharia principles because all practices are still based on the DSN-MUI and KHES (Compilation of Sharia Economic Law) fatwas. If there is confusion in the contract, the bank will conduct an audience with the customer. The second increase in installments in the payment tenor for the Griya Simuda KPR product occurred due to several factors, namely adjustments to the margin (profit) which refers to the interest rate system which can change at any time depending on inflation, the profit target to be achieved and profit sharing with third parties. The high margin is to anticipate rising market interest rates or inflation so that if there is a large increase in interest rates, the bank will not experience real and significant losses.